PROPAGANDA POLITIK POPULISME: KEBERHASILAN FREIHEITLICHEN PARTEI ÖSTERREICHS (FPO) DALAM PEMILIHAN LEGISLATIF NASIONAL AUSTRIA 2017 - Kusuma, Nyoman Giri; Suwecawangsa, Adi Putra; Nugraha, A.A Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 2 No 2 (2023): Jurnal DIKSHI, 2023)
A right-wing party in Austria, namely the Freiheitlichen Partei Osterreichs (FPO) with a populist movement that surprisingly gained a significant number of votes in the Austrian National Legislative Election in 2017. This increase in votes is quite large for the far-right party, who has a bad history in Austrian politics. To answer the question regarding the efforts of the FPO party in attracting voter sympathy in the 2017 Austria legislative elections, researcher use the conceptual framework such as Populism and Propaganda.  Furthermore, this research use qualitative-descriptive research methods with secondary data sources through library research.  This research examine that the party led by Heinz Cristian Strache gain popularity when there were issues surrounding asylum seekers immigrants who came to Austria in large numbers.  This issue has become the object of populist propaganda to spread the message that immigrants are a source of problems that burden the country and the lives of the Austrian people. Through the Propaganda approach, FPO contributes to shape the opinion of the majority Austrian people to secure voting rights holders for their party.   Keywords : Freiheitlichen Partei Österreichs, Imigran, Populisme, Propaganda.